Molecular traits to elucidate the ancestry of Helianthus x multiflorus. (February 2015) - Frey, Maximilian; Spring, Otmar
Abstract: The triploid perennial Helianthus x multiflorus L. is a beloved garden ornamental, but its phylogenetic origin has long been a source of discussion. Sequence comparison of genes involved in the biosynthesis of the sesquiterpene lactones was used to identify the common sunflower Helianthus annuus L. and the diploid taxon Helianthus decapetalus L. as the most likely parental combination in the origin of the triploid hybrid species. A pair of deletions (22 and 26 bp in length) in an intron part of the germacrene A synthase 1 gene differentiated the diploid from the tetraploid karyotype of H. decapetalus . The same deletion was found in one of the two alleles (299 bp in length) in H. x multiflorus, whereas a second allele (350 bp in length) showed a very high similarity with the sequence found in H. annuus . Quantification of the two amplification products in H. x multiflorus showed a higher concentration of the larger amplicon thus suggesting that H. annuus has contributed an unreduced genome to the hybrid. Comparison of variable regions of the cpDNA showed highest identity of H. x multiflorus with cpDNA sequences of the diploid H. decapetalus . This suggests that H. decapetalus served as the maternal parent in a cross with H. annuus to produce H. x multiflorus . Highlights: The hybridization background of Helianthus x multiflorus (3n) has been elucidated. Helianthus annuus and Helianthus decapetalus (2n) were revealed as parental species. Comparison of cpDNA provided additional information on the maternal parent species.